Immunomodulatory properties of porcine, bone marrow-derived multipotent mesenchymal stromal cells and comparison with their human counterpart - Comite, P.; Cobianchi, L.; Avanzini, M. A.; Mantelli, M.; Achille, V.; Zonta, S.; Ferrari, C.; Alessiani, M.; De silvestri, A.; Gandolfo, G. M.; Inverardi, L.; Brescia, L.; et al. (Cellular and Molecular Biology, 2011)
Thanks to their immunonodulatory properties, multipotent mesenchymal stromal cells (MSCs) are a promising strategy for preventing/reducing the risk of graft rejection after hematopoietic cell and solid organ transplantation. We have previously demonstrated that porcine MSCs (pMSCs) can be isolated from bone marrow and display similar morphology and differentiative capacity as compared to human MSC (hMSCs). In this study, we investigated the in vitro immunomodulatory properties (namely the ability to suppress lymphocyte proliferation in response to phytohemagglutinin and the cytokine production in the culture supernatants) of pMSCs from six Large White 6-month old piglets. Similarly to hMSCs, pMSCs reduced the phytohemagglutinin-induced lymphocyte proliferation. High levels of IL-6 were found in culture supernatants, whereas IL-10 and TGF-Î² were not detectable. In conclusion, ex vivo expanded pMSCs share selected biological/functional properties with hMSCs. pMSCs may be used in in vivo models to investigate novel approaches of prevention of graft rejection in solid organ transplantation.